A prospective study of headache and neuropeptides in patients with pituitary adenomas. (July 2019) - Zhang, Yixin; Pan, Qi; Jiang, Huahua; Yang, Gang; Chen, Lixue; Qin, Guangcheng; Zhou, Jiying
Objective: To evaluate clinical criteria for headache associated with pituitary adenoma (HaPA) in the International Classification of Headache Disorders (ICHD) 3rd edition version criteria and further determine whether elevations of plasma calcitonin gene-related peptide and pituitary adenylate cyclase-activating peptide 1-38 (PACAP1-38) concentration contribute to HaPA. Methods: Demographic and clinical features of consecutive patients with pituitary adenoma were recorded. Plasma calcitonin gene-related peptide and PACAP1-38 concentrations in pituitary adenoma patients within 72 h pre- and post-operation were measured. Primary outcome for HaPA patients were 50% reduction of moderate-to-severe headache days at 3 months after discharge. Results: Sixty-three patients with pituitary adenoma were recruited, 33 (52.4%) of whom had headache. The patients who had HaPA presented with migraine-like (32.9%), tension-type-like (12.1%), and stabbing headache (9.1%). Non-functional adenoma was present in the majority of cases (82.5%). Surgical resection improved headache in 83.3% of cases at 3 month follow-up. Pre- and post-operative calcitonin gene-related peptide and PACAP1-38 levels were significantly higher in patients with headache than in those without headache ( p  < 0.05). Plasma calcitonin gene-related peptide and PACAP1-38 levels at 72 h post-operation were lower at 72 h after operation in patients who had greater improvement in headache compared with those who had little improvement, while plasma calcitonin gene-related peptide and PACAP1-38 levels were similar between these two groups preoperatively. Conclusions: Most pituitary adenoma patients have non-functional adenoma, and half of this group have HaPA, indicating that the ICHD-3 criteria for HaPA with the emphasis on secretion status need further modifications. Lower plasma calcitonin gene-related peptide and PACAP1-38 concentrations at 72 h after operation may predict a better outcome in patients with HaPA.